EVALUATION OF OPERATIONAL PARAMETERS AND ITS RELATION ON THE STOICHIOMETRY OF FENTON'S OXIDATION TO TEXTILE WASTEWATER - Ilhan, Fatih; Yetilmezsoy, Kaan; Kabuk, Harun Akif; Ulucan, Kubra; Coskun, Tamer; Akoglu, Busra (ASSOC CHEMICAL ENG, 2017)
The operation conditions for the implementation of the Fenton process are of utmost importance because there are problems related to the proportion of H2O2 dosage to COD and Fe2+ dosage to the specified H2O2 amount. The relevant literature shows that COD/H2O2 ratios range between 0.0084 and 113.9. Similarly, the COD/Fe2+ ratio varies between 0.079 and 2926, while the H2O2/Fe2+ ratio varies between 0.09 and 287 Moreover, the ratio of the maximum value to the minimum value used in the operations on the basis of COD is 13560 for COD//H2O2 (0.0084-113.9), 2210 for COD/Fe2+ (0.079-174.7), and finally 3190 for H2O2/Fe2+ (0,09-287). The aim of this study was to re-evaluate these values that significantly differ from each other with specific emphasis on textile wastewater and considering stoichiometric ratios. Results showed that values ranging between 0.43 and 40 for COD/H2O2 and those ranging between 0.75 and 3.0 for H2O2/Fe2+ are more suitable. The results showed that in a Fenton process conducted by dosing H2O2 at different times, the TOC reduction efficiencies increased from 80.8 up to 88.9%. Similarly, the color reduction efficiency also rose from 96.5 to 98.7%.
Keywords: Fenton's oxidation; operational parameters; oxidation; stoichiometric ratio; TOC removal; PREOXIDATION; OPTIMIZATION; PRETREATMENT; COAGULATION; LEACHATE; CARBON; COD; Chemistry; Engineering